Hybrid Decision Making Model-Unitising for the Analysis of Competitive Intelligence, Green Marketing and Green Purchase Intention in the Pursuit of Sustainability - Salehi, Farbod; Gholamveisy, Soma; Rostamzadeh , Reza; Saparauskas, Jonas; Turskis, Zenonas (Transformations In Business & Economics, 2026)
With intensifying global competition and increased consumer desire for sustainable products, organisations must now incorporate competitive intelligence, green marketing, and green purchase intentions into a simultaneous process involving multiple criteria decision-making (MCDM). Most research on this topic has investigated one of these factors at a time and no model has been developed to demonstrate their congruent relationship in a fuzzy decision-making process. This lack of an integrated model does not allow for a full examination of these factors regarding sustainability and sustained competitive advantage. In this research, an integrated approach that employs fuzzy multi-criteria decision-making (FMCDM) techniques to assess and rank sustainability strategies is proposed. The fuzzy Delphi technique was employed to determine 24 criteria grouped across four dimensions competitive intelligence, green marketing, green purchase intention and sustainability and validate that with identified experts. Then, the criteria were employed in the analysis of four strategic alternatives: supply chain transparency, value-based green marketing, reduction of resource consumption, and investment in green innovation which were analysed within three FMCDM methods SECA, COCOSO and MARCOS. The robustness of results was confirmed through sensitivity analysis and cross-method comparison. Findings indicate that that investing in green innovation is the most effective strategy for increasing brand value and reducing environmental impact. Supply chain transparency and resource consumption reduction are next in priority. Raising the importance of green purchase intention emphasises supply chain transparency. The model offers managers a practical framework to prioritise sustainability strategies amid market uncertainties, and companies like P&G can use it to boost green initiatives and customer loyalty.